Pendugaan Komponen Ragam dan Heritabilitas Karakter Kuantitatif Cabai (Capsicum annuum L) - Hakim, Abdul; Syukur, Muhamad (Jurnal Agro Teknologi Tropika, 2015)
Chili is one commodity that is widely consumed vegetable Indonesian society. Assembling a variety with a specificpurpose requires genetic information about the characters wanted. One way to obtain genetic information is throughthe estimation of variance components and heritability. The purpose of this study was to estimate the variance andheritability of quantitative characters in chili. This research was conducted at the experimental Leuwikopo, Departmentof Agronomy and Horticulture IPB, Bogor Darmaga from April to September 2009. The population used a total of 17genotypes Collection Genetics and Plant Breeding Laboratory, Department of Agronomy and Horticulture. Genotypesused were IPB C2, IPB C4a, C5a IPB, IPB C10, C14 IPB, IPB C15, C19 IPB, IPB C20, C105 IPB, IPB C110, C126 IPB, IPBC128, C129 IPB, IPB IPBC131 C130, C132 IPB, and IPB C133. The experiment was arranged in a randomized completeblock design (RCBD) single factor with 2 replications. The results showed that the characters have a value of broadgenetic diversity are high dichotomous, plant height, crown width, stem diameter, flowering time, the time of harvest,fruit weight per plant, weight per fruit, fruit length, fruit diameter of the center, and the number of fruits per plant forquantitative and all characters have broad sense heritability values are high. This suggests that the genetic influenceis greater than the influence of the environment on the genotype.